Pengaruh Sharia Compliance dan Islamic Corporate Governance terhadap Kinerja Keuangan Perbankan Syariah - Hanny Fauziah Afdal; Henri Agustin (Jurnal Eksplorasi Akuntansi, 2023)
The purpose of this study was to determine the effect of sharia compliance and Islamic corporate governance rate on financial performance in Islamic banks in Indonesia in 2017-2021 and the sample in this study is 6 banks with a 5 years research period so that the total sample used in this study amounted 30. The sample in this study was obtained by using purposive sampling method. The research method uses an associative approach quantitative and SmartPLS software is used for data processing. This study found that there was a significant effect between sharia compliance on green banking disclosure practices in Islamic banks in Indonesia and did not find any influence between Islamic corporate governance on financial performance in Islamic banks in Indonesia. Recommendations for further research are to using proxies or other independent variables that have a stronger influence on Islamic banking financial performance, Develop or increase Islamic corporate governance indicators, Extending the reporting period for research samples.